Efficacy Of Sedomil 72 WP And Recozeb 80 WP In Controlling Red Rust Of Tea (Bangladesh Journal of Agricultural Research, 2011)
An experiment was conducted for two years to find out the efficacy of two fungicides Sedomil 72 WP (Mancozeb) and Recozeb 80 WP (Mancozeb + Metalaxyl) @ 1, 1.5, 2.0, and 2.5 kg/ha in controlling red rust disease (Cephaleuros parasiticus) of tea. in both the years, Sedomil 72 WP and Recozeb 80 WP inhibited disease severity and disease progress. Among the treatments, the highest reduction in PDI was obtained with 2.5 kg/ha of the both fungicides. During 2008, Sedomil 72 WP showed 93.28% and Recozeb 80 WP showed 91.04% efficacy with the dose of 2.5 kg/ha of both fungicides, while it was 91.40% of both with same dose during 2009. In case of the dose of 2.0 kg/ha of both the fungicides caused disease reduction more than 80%, which is significantly similar to the dose of 2.5 kg/ha. Decreasing trend in disease infection was observed from the spray to final sprays of both the fungicides for all doses. The overall result suggests that the use of Sedomil 72 WP or Recozeb 80 WP may provide an economic advantage alone with 2.0 kg/ha. Keywords: Efficacy of Sedomil 72 WP; Recozeb 80 WP; red rust of tea. DOI: http://dx.doi.org/10.3329/bjar.v36i2.9255 BJAR 2011; 36(2): 279-284